Peningkatan Hasil Belajar Soal Cerita KPK dan FPB dengan Pendekatan Pendidikan Matematika Realistik di Kelas V Sekolah Dasar - Dhanny Kurnia; Melva Zainil; Harni Harni (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this research is to improve the learning outcome from the student in Smallest multiples and biggest allience factor story question which  using Mathematic Realistic Education at Fivth grade student  from elemantary school of 25 Air Dingin Solok District. The subject at this research is the student from elementary school of 25 Air Dingin Solok District. The data from this research obtained from the result of observation on the action from the student. The results of each cycle are : (a) the teacher aspects increased from 78,57% to 96,43%, and the student aspect from 75% to 96,43%. (b) The learning score increased from 77,27 to 88,32. The Realistic Mathematic Education approach can improve student learning outcomes in social science knowledge fivth grade student from  elementary school of 25 Air Dingin Solok District.Key words : Learning Score Smallest multiples and biggest allience factor ; Realistic Mathematic Education approach